Fiscal Federalism and Wage-Related Industrial Unrest in the Public Service in Nigeria (Global Journal of Human-Social Science, 2015)
Wage-related industrial conflicts which manifest mainly in the form of strike actions have become recurring decimals in the public service in Nigeria. The frequency of these conflicts has become worrisome as a result of their disruptive tendencies in the country's industrial relations system. These conflicts that most often degenerate to industrial unrest have been partly attributed to absence of fiscal federalism in Nigeria, a situation that has ensured that the component units of the Federation do not have autonomy with respect to the control of resources located in their domains. The federating units have to always collect their fiscal allocation on monthly basis from the centre. Wage-related issues are also domiciled in the exclusive legislative list where only the Federal Government has prerogative. The fallout of all these is that today many of the federating units find it difficult to pay the National Minimum wage, salaries and wages of workers, and also meeting up with other financial commitments to workers. This situation frequently leads to industrial unrest in the country's public service. The paper therefore interrogates the relationship between absence of fiscal federalism in Nigeria and the frequent industrial unrest in the public service. The paper also makes recommendations that could prove helpful in ameliorating the situation.
Keywords: fiscal federalism; wage- related industrial unrest; industrial conflict; and public service